Kiai and Economic Independence: Kiai’s Strategy in Realizing the Independence of Darul Fiqhi Islamic Boarding School Lamongan, East Java - Miftahal Anjar; Moh. Ah. Subhan ZA (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
Kiai as the person who is most responsible for the journey of the pesantren certainly has a big contribution to the independence of the pesantren, because in the structure of the boarding school Kiai is the highest leader and has enormous authority. The role of the Kiai is one of the important factors behind determining the future direction of the pesantren, one of which includes the economic independence of the pesantren. The objectives of this research were the Kiai’s strategy in the economic independence of the pesantren, and the second, the factors that shaped economic independence in Islamic boarding schools. The focus of the location in this research was Darul Fiqhi Islamic Boarding School, Lamongan, East Java. This research was qualitative research. The data collection techniques used were observation, interviews and documentation, while the data analysis method used descriptive analysis. Based on the research conducted, it was known that: first, the role of the Kiai in the economic independence of the pesantren was that the Kiai acted as a giver of ideas or ideas, stockholders, advisers, management controllers, motivators, and decision makers in various regulations that in the managed business unit. Second, the kiai’s strategy in building the economic independence of the pesantren was to provide an understanding of the economy to the santri, empowering the santri, organizing the pesantren, building business units, as well as collaborating with parties outside the pesantren and the support and trust given by the community around the pesantren, such as being a member of the consumers and investors, as well as employees in business units owned by Islamic boarding schools.